Weed science research in India - BHAN, V M; KUMAR, SUSHIL (The Indian Journal of Agricultural Sciences, 2013)
Indian economy is primarily an agrarian one. Agricultural production depends on various factors and any set-back, in these factors severely aileets the yield of crops. Among all the pests (insects, animals, diseases and weeds) in India, weeds alone are responsible for one-third loss in crop production. Weeds in general reduce crops’ yield by 20-30% but as the farmers adopt some kind of weeding practices lin their fields, a conservative estimate of 10% loss may be taken as more realistic. In India, till seventies, manual and mechanical removal was one af the best options available with the farmers to manage weeds in their fields but’with the advent of labour cost, herbicides use started to get preference over manual weeding particularly in Punjab and Haryana, and now good amount of herbicides is being produced and utilized in India. In the seventies, biological control also started to take shape for weed control and in eighties good success was achieved to control water-hyacinth (Eichhornia crassipes Solms). and water-fern (Salvinia molesta). This paper deals with various weed problems and on going researches in different branches of weed science and different management options fbr terrestrial, aquatic and parasitic weeds in context to indian situations. Issues, priorities and perspectives of research for weeds management are also discussed.